Study of Gastropod Community Structure After Development of Tourism Activities on the Senjoyo River - Marsahanda Astri Ramagita; Sucahyo Sucahyo; Desti Christian Cahyaningrum (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2023)
It is thought that the development of the Senjoyo River as a tourist attraction in Semarang Regency will cause changes to the natural ecosystem in the area, one of which is changing the structure of the existing gastropod community. This research is a quantitative analysis research using a survey method that aims to examine the structure of the gastropod community after the development of tourism activities on the Senjoyo River. Gastropod samples were taken from 10 different observation stations along the Senjoyo River, which are located at 7˚22'23